Shimmy shimmy coke-ca-pop! : A collection of city children's street games and rhymes - Langstaff, John. 1920-2005.; Langstaff, Carol; MacSorley, John (Garden City, N.Y. : Doubleday, 1973)
Photographs and text introduce a variety of games with or without music.
Keywords: Games -- United States -- Juvenile literature; Children's poetry; Games with music